UZBEKISTAN IN ISSUES OF GENDER EQUALITY - Begamova Nasiba Kholmurzayevna (Scholar Express Journal, 2024)
In the article, in the following years, honoring the women of Uzbekistan and increasing their role in society has become one of the important directions of the state policy, for this purpose, a number of legal documents representing the interests of women have been adopted, and many social privileges have been introduced for women
Keywords: family; woman; society; gender